Effects of Outsourcing on National Forest Plantation Development Programme in Ghana (Asian Business Research, 2017)
The study aimed at management of outsourcing of National Forest Plantation Development Programme (NFPDP) and its effects in the Atebubu Forest District as a case study in Ghana. The key issues examined are the level of technical competence of the contractors, the role of the lead implementing agency and the natural resource base sustainability. Two stage sampling technique was used to sample one hundred and ten respondents for the study. A structured questionnaire was used to solicit information from the respondents. Descriptive and inferential statistics were used to analyse the data. The results of the study indicate that the award of seedlings contracts and workers‟ salaries and logistics to African Foresters Brigade and Zoil Ghana Limited respectively were transparent. However, most of the activities the participating institutions performed were behind schedule indicating poor performance. It is therefore recommended that, Forestry Commission should put in place proper modalities to ensure effective implementation if outsourcing is to be continued.